THE IMPLEMENTATION OF SELF-ASSESSMENT IN EFL STUDENT’S SPEAKING PERFORMANCE - Munawaroh Alfianti (FKIP, Universitas Banten Jaya, 2022)
A lot of EFL students feel unconfident in performing their English-speaking performance and do not have a decent engagement in self-reflection of their speaking performance development. Self-assessment is one of the assessment techniques that requires students’ participation in its process. The study was conducted to explore whether the implementation of self-assessment results a significant difference in EFL students’ speaking performance. The researcher conducted a quantitative study with a Posttest-Only Control Design. 34 first-year EFL students became the participants in this study. Seventeen students took part in an experimental group and the other seventeen students took part in a control group, in English department at a university in Surabaya, Indonesia. The researcher analyzed data using an Independent Samples t-test. The findings of the Independent Samples t-test indicate that there is a significant difference in experimental group students’ speaking performance after implementing self-assessment. Thus, the teachers are recommended to promote the use of self-assessment in facilitating students’ speaking performance Keywords: speaking performance, self-assessment, EFL student, English-speaking, E-portfolio